Our struggle with Information and Communication Technologies (Journal of Parents and Teachers, 2022)
The development of a digital transformation in a school is complex and at the same time a thrilling process. In this article we share our digital journey. Our experience has contributed to make us find technology as a facilitator of the work of all those involved in the learning process. Focusing on the students, there is clear evidence that technology has extremely contributed to create the profile of the new student: self-sufficient, capable of managing their own leaning process and distinguish correctly among the vast quantity of information they have access to.
Keywords: technology; learning; learning innovation; new technologies; learning technology; technical staff; teaching staff